THE EFFECTIVENESS OF VISUAL COMMUNICATION VIDEOS IN LEARNING THE PRODUCTION OF CARBON USING JENGKOL SKIN IN HIGH SCHOOL STUDENTS - Nadia Amalia; Irman Suherman (Dian Nuswantoro University, 2025)
The purpose of this research is to determine the difference in the effect of the experimental exposure method using video visual communication in the experimental class and using conventional methods as a control class on the learning outcomes of vocational school students. Understanding the concept of carbon as absorbent which is useful for reducing liquid waste which is harmful to the human environment, especially in facing the SDGs goals. The subjects of this research were 40 class XI vocational school students The students were divided into two classes, namely the control class and the experimental class. That The learning outcomes of both classes are measured from pre-test and post-test scores as well as N-Gain. To test the hypothesis using the Independent Sample T-test. The research results show that it is practical exposure methods are more effective than conventional methods. This is proven by the N-Gain value for the experimental class is greater than the control class. Strengthened by results statistical test with the Independent Sample T-test where the sig value. (2 tails) < 0.05. So that The impressive method of experimentation using video displays results improves understanding, providing more insight real experience and obtain better learning outcomes. Expected Believed experimental experimenthas an influence on student learning success.